The double burden of COVID-19 and a major volcanic eruption on local food production and food security in a Small Island Developing State - Augustus, Eden; Murphy, Madhuvanti M.; Guell, Cornelia; Morrissey, Karyn; Ramdath, Dan; Woodward, Mark; Anderson, Simon G.; Unwin, Nigel (Frontiers in Sustainable Food Systems, 2023)
Introduction: Small Island Developing States have disproportionately high food insecurity rates, related to complex challenges and vulnerabilities. The COVID-19 pandemic highlighted that within these settings, crises often overlap. We aimed to assess the impact of the concurrent COVID-19 pandemic and volcanic eruption on food production and security in St. Vincent and the Grenadines (SVG).Methods: An interpretive mixed-methods study was conducted among a convenience sample of consenting adults ≥18 years from 100 households in SVG through a cross-sectional survey and participant interviews (10 households) between September 2021 and March 2022. Food insecurity prevalence over the past year was assessed using the Food Insecurity Experience Scale (FIES) (Rasch modelling) and impacts to livelihoods from the pandemic and volcanic eruption was assessed using an adapted Caribbean COVID-19 Food Security & Livelihoods Impact Survey (Caribbean COVID-19 FS&L Survey). Data were analysed using logistic regression.Results: During the pandemic, 59% of the participants reported decreased income, 63% had no access to markets, 81% had no access to food aid; 34% of the participants had a change in food sources, and 81% reported that food production was negatively impacted by the volcanic eruptions, of which 68% reported decreased food production. The interviews highlighted that access to markets were restricted by fear of leaving home and contracting the COVID-19 virus, and participants who received food aid stated that the number of items were not sufficient for larger families. Almost half of the participants were severely food insecure (48% (95% C.I. 31.2,57.8)); almost two thirds were moderately to severely food insecure (64% (95% C.I. 50.0, 74.2)); mean FIES score 5.31 (95% C.I. 5.0,5.6). After adjusting for gender, age, education, and household size, moderate to severe food insecurity was associated with no access to food aid during the pandemic and post-eruptions (odds ratio 3.7; 95% confidence interval 1.5, 9.1; p=0.004).Conclusion: Food insecurity rates were high during the COVID-19 pandemic, exacerbated by volcanic eruptions and insufficient access to food aid. Our results suggest the need for the development of strategies and interventions aimed at increasing the resilience of food systems to mitigate the effects of future disasters.